Use of Schiller’s test versus Pap smear to increase detection rate of cervical dysplasias - H. E., Ramaraju; Y. C., Nagaveni; Khazi, A. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Application of Lugol's iodine to cervix (Schiller's test) is named as Visual Inspection of cervix after applying Lugol's Iodine (VILI). VILI improves the detection rate of suspicious area over the cervix. The objectives of the study was to screening for early carcinoma or Dysplasia cervix by Schiller’s test & Pap smear and to compare the results of Schiller’s test with Pap smear results. Methods: The present prospective randomized control trials study was undertaken among 500 women aged between 25-65 years outpatient’s Department of gynecology in Vijayanagar Institute of Medical Sciences (VIMS) Bellary. The study was undertaken during January 2007 to June 2008. Permission for the study was obtained from the College authorities prior to commencement. Results: Out of total 500 patients screened for Pap smear and Schiller’s iodine, majority were in the age group of 31-40 years. Biopsy proven dysplasia was more common in patients with white discharge (10.8%), post-menopausal bleeding (16.6%) and in posts coital bleeding (15.3%). 180 cases were Schiller’s iodine test positive, out of which biopsy proven cases were more in non-specific chronic cervicitis (68.88%) and rest seen in cervical epithelial abnormalities ( 7.7%), Mild dysplasia (10%), Moderate and Severe dysplasia 13%. Cytological abnormalities were found in 48 (9.6%), 180 cases were Schiller’s iodine test positive (36%). Among these 180 Schiller’s positive cases 24 cases (13.33%) were CIN2 and CIN 3 lesions. 42 patients were Schiller’s test guided biopsy proven for cervical dysplasia, of which only 16 patients (8.88%) were Pap smear positive. The sensitivity of Schiller’s test and Pap smear were 97.67% and 38% respectively. Conclusions: This study reveals that Schiller’s test can be use full in low resource setting and in busy outpatient departments.